Polymorphisms in IL‐1A are associated with endometrial cancer susceptibility among Chinese Han population: A case–control study. (24th January 2020) - Liu, Ying; Sun, Yao; Wu, Jiamin; Xiong, Zichao; Du, Shuli; Niu, Fanglin; Jin, Tianbo; Guo, Ling
Abstract: Endometrial cancer (EC) is one of the most common malignant tumours of the female genital tract, and it has become a serious malignant disease of the female genital tract in China. Existing researches have revealed the association between polymorphisms of IL‐1A and several gynaecological diseases. In this research, we analysed the association between IL‐1A gene polymorphisms and endometrial cancer susceptibility in Chinese female population. A total of 81 patients and 198 healthy people were selected. Odds ratio (OR) and 95% confidence intervals (CIs) were calculated using unconditional logistic regression. Genetic models and analyses showed that IL‐1A rs3783550 TT and rs3783546 CC increased the risk of endometrial cancer under the recessive model, respectively (rs3783550: OR = 2.80, 95%CI: 1.32–5.92, p = .008; rs3783546: OR = 2.79, 95%CI: 1.32–5.89, p = .008). In the recessive model, we also found that both IL‐1A rs1609682 and IL‐1A rs3783521 increased the risk of endometrial cancer, respectively (rs1609682: OR = 2.79, 95%CI: 1.32–5.89, p = .0081; rs3783521: OR = 2.80, 95%CI: 1.32–5.92, p = .008). Haplotype analysis was performed that did not reveal any significant results. In summary, IL‐1A rs3783550, rs3783546, rs1609682 and rs3783521 polymorphisms may be associated with an increased risk of endometrial cancer in Chinese female populations.